Ultrasensitive Qβ Phage Analysis Using Fluorescence Correlation Spectroscopy on an Optofluidic Chip - Rudenko, M.I. (2009)
We demonstrate detection and analysis of the Qβ bacteriophage on the single virus level using an integrated optofluidic biosensor. Individual Qβ phages with masses on the order of attograms were sensed and analyzed on a silicon chip in their natural liquid environment without the need for virus immobilization. The diffusion coefficient of the viruses was extracted from the fluorescence signal by means of fluorescence correlation spectroscopy (FCS) and found to be 15.90±1.50 μm(2)/s in excellent agreement with previously published values. The aggregation and disintegration of the phage were also observed. Virus flow velocities determined by FCS were in the 60-300 μm/s range. This study suggests considerable potential for an inexpensive and portable sensor capable of discrimination between viruses of different sizes.